Ethical Joyce - Eide, Marian (Cambridge University Press, 2002)
Eide argues that the central concern of James Joyce's writing was the creation of a literary ethics. Eide examines Joyce's ethical preoccupations throughout his work, particularly the tension between his commitment as an artist and his social obligations as a father and citizen during a tumultuous period of European history.